New areas of distribution of some plant species in the basin of Sumgayitchay river in Azerbaijan - Alieva Dilruba Burkhan (Hortus Botanicus, 2019)
The results of the floristic research conducted during 2012-2014 in the flora of Sumgayitchay river basin are given in the article. During the research, the following species were collected and identified in the Sumgayitchay river : Sagina procumbens L., Delphinium freynii Conrath, Crambe orientalis L., Saxifraga cymbalaria L., Rubus candicans Weihe, Trifolium hirtum All., Astragalus brachycarpus M. Bieb., Euphorbia macroceras Fisch. et C. A. Mey., Scrophularia lateriflora Trautv. and Asperula caucasica Pobed. The species are absolutely new for the studied area. The morphological and ecological characteristics of the species are studied, as well as their natural ecosystems and phytocenoses.